(untitled) (Historia, 2021)
The South African Air Force (SAAF) played an important role in the Second World War and operated on many fronts. In the article detailed attention is given to the role played by the SAAF in the Warsaw Airlift - an operation with the objective of dropping supplies from the air to the Polish partisans in Warsaw, the capital of Poland. Statistical data is used to compare and evaluate the contribution of the SAAF in relation to that of the Royal Air Force (RAF) and Polish Special Duties Flight 1586, as well as to the single mission by the Americans. Both political and military aspects of the Warsaw airlift are taken into account in the process of drawing certain conclusions. This operation was a major Allied contribution to Polish civilian opposition to German aggression during the war.